C-type natriuretic peptide regulates sperm capacitation by the cGMP/PKG signalling pathway via Ca2+ influx and tyrosine phosphorylation. Issue 3 (March 2019) - Wu, Kejia; Mei, Chunlei; Chen, Yao; Guo, Lidan; Yu, Yuejin; Huang, Donghui
Abstract: Research question: What is the effect of C-type natriuretic peptide (CNP) on human sperm capacitation in vitro and what is the mechanism of this effect? Design: CNP/NPR-B expression in the female rat genital tract was examined by immunohistochemistry and western blot assay, and then the role of CNP in human sperm capacitation was determined. The signal transduction pathway of CNP in the process was determined to elucidate the regulation mechanism of CNP by enzyme-linked immunosorbent assay and flow cytometry. Results: Both CNP and NPR-B were expressed in the genital tract of female rats, especially in the mucosa epithelium cell of the oviduct; the CNP level in the rat oviduct was higher than that in the cervix. Both CNP and NPR-B level in the rat oviduct varied during the oestrus cycle, maximal expression being observed at proestrus. Furthermore, intracellular cGMP level in spermatozoa was significantly enhanced by CNP ( P  < 0.01). PKG activity was detected in the spermatozoa, and it can be activated by the CNP and 8-Br-cGMP (cGMP analogue). The PKG inhibitor KT5823 inhibited the effect of CNP on sperm hyperactivation and the acrosome reaction. Finally, Ca 2+ and tyrosine phosphorylation levels in spermatozoa were markedly improved by CNP and 8-Br-cGMP but significantly inhibited by the addition of KT5823 ( P  < 0.05). Conclusions: CNP secreted by the female genital tract might bind to NPR-B on the spermatozoa. It successively stimulated intracellular cGMP/PKG signalling, increased Ca 2+ and tyrosine-phosphorylated proteins, promoted hyperactivation and induced the acrosome reaction, which ultimately facilitated sperm capacitation.